A Web-Based Prediction Model for Overall Survival of Elderly Patients With Malignant Bone Tumors: A Population-Based Study - Tang, Jie; Wang, JinKui; Pan, Xiudan (Frontiers in Public Health, 2022)
Background: Malignant bone tumors(MBT) are one of the causes of death in elderly patients. The purpose of our study is to establish a nomogram to predict the overall survival(OS) of elderly patients with MBT. Methods: The clinicopathological data of all elderly patients with MBT from 2004 to 2018 were downloaded from the SEER database. They were randomly assigned to the training set (70%) and validation set (30%). Univariate and multivariate Cox regression analysis was used to identify independent risk factors for elderly patients with MBT. A nomagram was built based on these risk factors to predict the 1-, 3-, and 5-year OS of elderly patients with MBT. Then, used the consistency index (C-index), calibration curve, and the area under the receiver operating curve(AUC) to evaluate the accuracy and discrimination of the prediction model. Decision curve analysis(DCA) was used to evaluate the clinical potential application value of nomogram. Based on the scores on the nomogram, patients were divided into high- and low-risk groups. Kaplan-Meier (K-M) curve was used to test the difference in survival between the two groups of patients. Results: A total of 1641 patients were included, and they were randomly assigned to the training set (N=1156) and the validation set (N=485). The univariate and multivariate analysis of the training set suggested that age, sex, race, primary site, histologic type, grade, stage, M stage, surgery, and tumor size were independent risk factors for elderly patients with MBT. The C-index of the training set and the validation set were 0.779[0.759-0.799] and 0.801[0.772-0.830], respectively. The AUC of the training set and the validation set also showed similar results. The calibration curves of the training set and the validation set both showed that the observed value and the predicted value were highly consistent. DCA suggested that the nomogram had potential clinical value compared with traditional TNM staging. Conclusion: We had established a new nomogram to predict the 1-, 3-, 5-year OS of elderly patients with MBT. This predictive model can help doctors and patients develop treatment plans and follow-up strategies.